Assessing the Fungal Simultaneous Removal Efficiency of Carbamazepine, Diclofenac and Ibuprofen in Aquatic Environment - Kasonga, Teddy K.; Coetzee, Martie A. A.; Kamika, Ilunga; Momba, Maggy N. B. (Frontiers in Microbiology, 2021)
Unused pharmaceutical compounds (PhCs) discharged into the aquatic environment have been regarded as emerging pollutants due to potential harmful effects on humans and the environment. Microbial bioreme-diation is considered as a viable option for their removal from wastewater. The aim of this study was to assess the simultaneous removal of carbamazepine (CBZ), diclofenac (DCF) and ibuprofen (IBP) by previ-ously isolated fungi (Aspergillus niger, Mucor circinelloides, Trichoderma longibrachiatum, Trametes poly-zona and Rhizopus microsporus). The tolerance to PhCs was conducted by tracking the fungal mycelium mat diameters in solid media and its dry biomass in liquid media, at the drug concentration range of 0.1 to 15 mg/L. The fungal enzymatic activities were determined for lignin peroxidase (LiP), manganese peroxidase (MnP) and laccase (Lac), respectively. The PhC removal efficiency of the fungi was assessed in aerated batch flasks and the drug concentrations and intermediate compounds formation were determined by us-ing SPE-UPLC/MS. A tolerance over 70% was recorded for all the fungi at drug concentration of 0.1 mg/L. Manganese peroxidase was produced by all the fungi with very low amount of LiP, while all the enzymes were produced by T. polyzona. The pH of 4.3, temperature 37±1.5 °C and incubation time of six days were the optimum parameters for the fungal enzymatic activities. The best removal of CBZ (87%) was achieved by R. microsporus after ten days. Between 78% and 100% removal of DCF was observed by all the fungi af-ter 24 h, while 98% of IBP was removed after two days by M. circinelloides. Only a few intermediate com-pounds were identified after three days and disappeared after ten days of incubation. This study demon-strated that apart from the basidiomycetes, the ascomycetes and zygomycetes are also producers of lig-ninolytic enzymes and have the ability to biodegrade emerging pollutants such as PhCs.